Hollow Mesoporous Silica by Ion Exchange-Induced Etching Strategy for High Temperature Proton Exchange Membrane - Zhang, Aijing; Jiang, Shengjuan; Shan, Xuefei; Wang, Jia; Zhou, Mingzheng; Chai, Maorong (Frontiers in Energy Research, 2021)
Hollow mesoporous silica (HMS) has attracted significant attention for fuel cell applications. The mesopores in the shell can accelerate proton transport and the void in the center of the particle is advantageous for proton storage. However, the conventional methods for HMS fabrication are complicated, which is not conducive to scaling up the fabrication of HMS. In this work, a new, simple strategy to synthesize HMS has been developed via OH- ion exchange-induced etching of mesoporous silica (mSiO2). The mSiO2 immersed in an alkaline Na2CO3 solution led to an exchange of the Br- ions in the surfactant with the OH- ions in the solution, resulting in a high concentration of OH- ions in the mesoporous channels of mSiO2 close to the core, and a low concentration of OH- ions close to the surface. This demonstrated that the etching of the core of mSiO2 was induced, which extended from the core to the surface of the nanoparticles. Furthermore, the success of the ion exchange-induced etching process was demonstrated by the gradient distribution of the Na+ ion in mesoporous silica microspheres through microscopy. In addition, the proton conductivity of the phosphoric acid-impregnated HMS membrane at 180 °C under anhydrous conditions was found to be 0.025 S cm-1. These results demonstrate the simplicity of the ion exchange-induced etching strategy for the fabrication of HMS microspheres and its promising application in high temperature proton exchange membrane fuel cells.